Diversity and structure of bird and mammal communities in the Semiarid Chaco Region: response to agricultural practices and landscape alterations - Decarre, Julieta (Imperial College London, Gran Bretaña, 2019)
Tesis para obtener el grado de Doctor of Philosophy (PhD) en Life Sciences, del Imperial College London, en 2015